Peran Dana Alokasi Khusus Fisik Afirmasi terhadap Pembangunan Pendidikan Daerah Tertinggal di Indonesia - Hadi, Samsul; Mahi, Benedictus Raksaka (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2024)
Indonesia's education statistics show the education gap between regions is still high. This inequality is seen through a comparison of the education index between regions and the disparity in Gross Participation Rate (GER) at the elementary and junior high school at the district/city per province in 2020. This study examines how the development of the education sector in underdeveloped areas after the policy of providing affirmative Physical Special Allocation Fund (SAF) field of education. Using 3-year panel data, the results of the study show that the affirmative Physical Special Allocation Fund (SAF) field of education has a positive and significant impact on the development of the basic education sector (SD and SMP), this is evidenced by its significant impact on APK. The performance of regional financial management through the number of SiLPA/SiKPA proxies has an impact on the achievement of education sector development in underdeveloped areas, the greater the number of SiLPA/SiKPA it can have a negative impact.